PERANCANGAN MESIN PEMIPIL JAGUNG SEMI-OTOMATIS DILENGKAPI SISTEM VAKUM - yeremia bagas setiawan; Nurhadi; Trisma Jaya Saputra (ELEMEN : JURNAL TEKNIK MESIN, 2026)
"Maize (Zea mays L.) is a staple crop widely cultivated in tropical regions. Before processing, maize needs to undergo a threshing process to separate the seeds from the cobs. Manual threshing often requires significant time and labor, so a more efficient tool is needed. This study aims to design a semi-automatic maize thresher equipped with a vacuum system to help clean debris during the threshing process. The research method includes a literature review, numerical calculations, 3D design using SolidWorks 2022, and static simulation to analyze stress, deformation, and safety factor of the frame. The machine is designed with a frame size of 1360 × 540 × 800 mm and uses a 5.5 hp gasoline engine. The frame material uses ASTM A36, with loading on the engine and component supports. The simulation results show a von Mises stress of 80.38 MPa on the engine frame and 5.19 MPa on the component frame, with maximum displacement of 1.80 mm and 0.01 mm. The safety factor value of 3.11 indicates that the design is safe."